2004
DOI: 10.1007/s00114-003-0492-6
|View full text |Cite
|
Sign up to set email alerts
|

Trophic specialisations in alternative heterochronic morphs

Abstract: Polymorphisms are suspected of reducing competition among conspecifics in heterogeneous environments by allowing differential resource use. However the adaptive significance of alternative morphs has been poorly documented. The aim of this study is to determine food partitioning of two heterochronic morphs of the Alpine newt, Triturus alpestris, in mountain lakes. The morphs differ in the functional morphology of their feeding apparatus. Only paedomorphs are able to expel water during prey suction behind the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…In fact, Denoel [11] showed that paedomorphic Alpine newts were more successful in capturing three out of four elusive prey types [11]. Next to different capabilities for capturing elusive prey, also different prey preferences were found between morphs [11, 15]. Furthermore, it has been shown that paedomorphic and metamorphic Alpine newts from the same population partition their trophic habitats [14, 45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, Denoel [11] showed that paedomorphic Alpine newts were more successful in capturing three out of four elusive prey types [11]. Next to different capabilities for capturing elusive prey, also different prey preferences were found between morphs [11, 15]. Furthermore, it has been shown that paedomorphic and metamorphic Alpine newts from the same population partition their trophic habitats [14, 45].…”
Section: Discussionmentioning
confidence: 99%
“…If so, we would also expect higher flow rates in paedomorphs, resulting in higher peak velocities induced to the prey. Higher flow velocities induced by suction in paedomorphic Alpine newts could finally explain why they are more efficient in capturing elusive prey [11, 15].…”
Section: Introductionmentioning
confidence: 99%
“…This finding is not very surprising because the growth and life-history of newts (age at maturity, paedomorphosis vs. metamorphosis) rely on environmental factors that will vary across populations, such as temperature [18], drying risk [37], and food availability [38,39]. …”
Section: Discussionmentioning
confidence: 99%
“…low habitat heterogeneity; Skulason & Smith 1995). Indeed, the ability to exploit underused resources can lessen intraspecific competition and ultimately allow higher reproductive success, therefore accounting for the adaptiveness and long-term persistence of trophic polyphenisms in the same habitat (Bolnick, 2001;Denoël, Schabetsberger, & Joly, 2004;Schmidt, Bertness, & Rand, 2000). But such stable trophic polyphenisms are expected to be advantageous in conditions of high habitat heterogeneity (higher potential for niche availability and discordance; Skulason & Smith 1995;Wellborn & Langerhans 2015), as is the case with teleost and amphibian polyphenisms along the littoral-pelagic axis in lakes (Lejeune et al, 2018;Nosil & Reimchen, 2005;Recknagel et al, 2017;Smith & Skúlason, 1996;Wimberger, 1994).…”
Section: Progenesis As An Intrinsic Factor Of Ecological Opportunitymentioning
confidence: 99%
“…low habitat heterogeneity; Skulason & Smith, 1995). Indeed, the ability to exploit underused resources can lessen intraspecific competition and ultimately allow higher reproductive success, therefore accounting for the adaptiveness and long-term persistence of trophic polyphenisms in the same habitat (Bolnick, 2001;Denoël et al, 2004;Schmidt et al, 2000).…”
Section: Progenesis As An Intrinsic Factor Of Ecological Opportunitymentioning
confidence: 99%